2017
DOI: 10.3233/jad-170491
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Recover from Proactive Semantic Interference and Abnormal Limbic Connectivity in Asymptomatic, Middle-Aged Offspring of Patients with Late-Onset Alzheimer’s Disease

Abstract: The present results suggest that both semantic interference deficits and connectivity abnormalities might reflect limbic circuit dysfunction as a very early clinical signature of LOAD pathology, as previously demonstrated for other limbic phenotypes, such as sleep and circadian alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…Specifically, the second cued recall for both List A and List B were the strongest predictors of aMCI in logistic regression models and had a greater discriminatory power relative to delayed memory for passages, suggesting that evaluating semantic interference may be more powerful in detecting early features of Alzheimer's disease compared to other evaluations [21]. Other studies have found equivalent yet subtler semantic interference difficulties in asymptomatic middle-aged offspring of patients with Alzheimer's disease and such reduced performance was associated to structural changes in AD-relevant regions, increased amyloid load in the temporal lobe [41] and also exhibited inverse correlations with functional connectivity in limbic regions [42], providing evidence that deficits in semantic interference may represent ( * ) Indicates a significant difference of p < .05 between controls and one group of participants with a family history of Alzheimer's disease. structural and limbic circuit dysfunction in early pathophysiology of Alzheimer's disease and that the LASSI-L should therefore be especially sensitive to subtle cognitive impairments in individuals with a family history of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the second cued recall for both List A and List B were the strongest predictors of aMCI in logistic regression models and had a greater discriminatory power relative to delayed memory for passages, suggesting that evaluating semantic interference may be more powerful in detecting early features of Alzheimer's disease compared to other evaluations [21]. Other studies have found equivalent yet subtler semantic interference difficulties in asymptomatic middle-aged offspring of patients with Alzheimer's disease and such reduced performance was associated to structural changes in AD-relevant regions, increased amyloid load in the temporal lobe [41] and also exhibited inverse correlations with functional connectivity in limbic regions [42], providing evidence that deficits in semantic interference may represent ( * ) Indicates a significant difference of p < .05 between controls and one group of participants with a family history of Alzheimer's disease. structural and limbic circuit dysfunction in early pathophysiology of Alzheimer's disease and that the LASSI-L should therefore be especially sensitive to subtle cognitive impairments in individuals with a family history of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Test-retest reliabilities of the LASSI-L have been shown to be high in previous studies (r = 0.60 to r = 0.89) among aMCI and early dementia, and the accuracy of classification of older adults with MCI versus cognitively normal has exceeded 90% [26] , [27] . The LASSI-L has demonstrated adequate test-retest reliabilities, and high discriminative and concurrent validity [15] , [16] , [17] , [26] , [27] .…”
Section: Methodsmentioning
confidence: 99%
“…Recent preliminary work by Sanchez et al. [17] in Buenos Aires, Argentina, studied performance on the LASSI-L among Hispanic middle-aged asymptomatic children of patients with late-onset AD. Notably, frPSI deficits differentiated this at-risk group from age-equivalent controls without a family history of late-onset AD and were related to decreased brain connectivity on functional magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…The Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L) is a novel test first developed with the aim to detect preclinical and prodromal stages of Alzheimer's disease (18). Several studies have been conducted in the setting of Alzheimer's disease, showing a high diagnostic accuracy and a correlation with amyloid load, limbic connectivity, and brain volumes involved during the first stages of Alzheimer's disease (19)(20)(21)(22). Furthermore, the LASSI-L has shown to be superior to the Free and Cued Selective Reminding Test (FCSRT) in the prediction of Alzheimer's disease features on 18 F-Fluorodeoxyglucose positron emission tomography imaging (23).…”
Section: Introductionmentioning
confidence: 99%
“…These cues along with the 1:1 competing targets on the LASSI-L also serve to elicit considerably more proactive and retroactive semantic interference and semantic intrusion errors. These semantic deficits, and especially semantic intrusions have been associated with increased risk of neurodegeneration and frontal executive hypoactivation on fMRI in middle-aged offspring of patients with late-onset Alzheimer's disease, which may suggest deficits in source memory and disinhibition (19)(20)(21)(24)(25)(26). The CVLT does measure proactive interference because it has a group words on List B that semantically compete with List A.…”
Section: Introductionmentioning
confidence: 99%